2015
DOI: 10.1111/jcpp.12395
|View full text |Cite
|
Sign up to set email alerts
|

Pathways from maternal depressive symptoms to adolescent depressive symptoms: the unique contribution of irritability symptoms

Abstract: BackgroundThe authors tested three possible pathways linking prenatal maternal depressive symptoms to adolescent depressive symptoms. These pathways went through childhood Irritability Symptoms, Anxiety/Depressive Symptoms or Conduct Problems.MethodData were collected from 3,963 mother–child pairs participating in the Avon Longitudinal Study of Parents and Children. Measures include maternal depressive symptoms (pre‐ and postnatal); toddler temperament (2 years); childhood (7–13 years) irritability symptoms, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 61 publications
4
36
1
1
Order By: Relevance
“…Consistent with homotypic continuity, preschool depression predicts MDD later in childhood and adolescence 4143 . However, evidence also suggests that preschool depression predicts anxiety disorders and ADHD in later childhood as well 41,44 .…”
Section: Prevalence and Course Of Preschool Depressionmentioning
confidence: 79%
See 1 more Smart Citation
“…Consistent with homotypic continuity, preschool depression predicts MDD later in childhood and adolescence 4143 . However, evidence also suggests that preschool depression predicts anxiety disorders and ADHD in later childhood as well 41,44 .…”
Section: Prevalence and Course Of Preschool Depressionmentioning
confidence: 79%
“…Other work has focused on the heritability/genetics 5760 associated with early-onset depression and more specifically, a large body of literature has linked parental history of depression and related psychopathology to preschool-onset depression in their children 29,42,43,61,62 . For example, a recent epidemiological study found two distinct pathways linking pre- and post-natal maternal depression to adolescent depressive symptoms, one pathway through preschool irritability symptoms and another through preschool anxiety/depressive symptoms 43 .…”
Section: Factors Associated With Preschool Depressionmentioning
confidence: 99%
“…Correlations with only the control or ECSS groups indicate that the changes in those genes mediate behavioral variation within the control or ECSS group, but that the changes are not directly associated with the between group differences or variation in the other group. The gene and protein expression and robust behavioral correlations support increased focus on vasopressin, ghrelin, orexin and changes in both glucocorticoid and mineralocorticoid receptors in both animal and clinical studies of the adverse effects of early life stress, especially those focusing on depression and anxiety in mothers and transgenerational effects on offspring (Apter-Levy et al, 2013; Feldman et al, 2009; Whelan et al, 2015). …”
Section: Discussionmentioning
confidence: 93%
“…One possibility is that mothers with a history of depression may be more likely to engage in parenting practices that may maintain or exacerbate the emotional reactivity characteristic of early irritability throughout development. That is, highly irritable children of depressed mothers may fail to receive parenting that bolsters the development of the self-regulatory skills that can buffer against a propensity for heightened emotional reactivity (Whelan et al, 2015). Alternatively, given evidence that symptoms of irritability show moderate stability (Leibenluft et al, 2006), it is also plausible that irritability’s association with the ΔLPP may be the result of its current rather than early manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, irritability can be an early precursor to adolescent and adult depressive disorders (Vidal-Ribas, Brotman, Valdivieso, Leinbenluft & Stringaris, 2016), although many depressed adolescents and adults do not have a history of childhood irritability (Stringaris et al, 2010; Stringaris & Taylor, 2015). Moreover, Whelan and colleagues (2015) recently found that childhood irritability uniquely mediated the relationship between maternal depressive symptoms and the later development of adolescent depression over and above childhood anxiety and depressive symptoms. Taken together, these data raise the possibility that irritability may mark a distinct pathway in the development and intergenerational transmission of depression.…”
mentioning
confidence: 99%